Komplex football training's influence on the qualitative changes of the basic motor abilities - Jeleskovic, E.; Talovic, M.; Alic, H.; Bajramovic, I. (Acta Kinesiologica, 2008)
Main goal of this research is to determine the level of change in basic motor abilities with footballers who are undergoing one year training process. Research included 107 16 and 17 years old footballers actively training and playing in cadet`s championship. 17 tests of abilities have been used to evaluate the basic motor abilities: explosive power, speed, coordination, repetitive power, flexibility and balance. Tests were standardized and publicized. The program lasted for a year and its main feature was the mixture of working methods where the training processes were designed in a way that drill trainings and no ball trainings were dominant. We have analysed the qualitative changes in the structure of the basic motor abilities in football and the differences in the structure of the covariance matrix of the manifest and latent variables in two places in time, from which the component model of the factorial analysis is derived. After the results are analysed we can say that a year of a training program lead to changes in transformation of a basic motor abilities, as well as to positive qualitative changes in the structure, position and the number of latent dimensions, as well as in hierarchical subordination of the centers for the structure of swinging.